Stile dalam Novel Si Anak Spesial Karya Tere Liye: Analisis Bahasa Sederhana dan Cerita Saduran dalam Sastra Anak - Haula Lutfia; Lina Sundana (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study aims to collect, analyze, and expand the theory of style contained in the novel Si Anak Spesial by Tere Liye, focusing on stylistic features that characterize children’s literature in the text. The study examines how stylistic elements are constructed through simple language and adapted narrative forms within the novel. The method used in this study is descriptive qualitative using a stylistic approach. The data in this study include phrases, sentences, and conversations. The data source in this study comes from the novel entitled Si Anak Spesial by Tere Liye. Data collection techniques in this study include literature studies, notes, and analysis. The data analysis stage in this study includes three steps: data reduction, data presentation, and conclusion drawing. The findings reveal 15 stylistic data consisting of five instances of simple lexical language, five instances of simple syntactic structures, three instances of adapted narrative forms in the form of phrases, and two instances of adapted characterization patterns. The analysis shows that the stylistic construction of the novel is dominated by simple syntactic structures and adapted narrative elements, which function to facilitate comprehension for child readers. These stylistic characteristics demonstrate how linguistic simplicity and narrative adaptation operate as key strategies in shaping children’s literature.